IMPLEMENTASI SISTEM INFORMASI MANAJEMEN KEUANGAN DAERAH BADAN PENGELOLA KEUANGAN DAN ASET DAERAH KABUPATEN BUNGO - Eryasi Daryati (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
The application of the SIMDA Financial application to the Bungo Regency Regional Financial and Asset Management Agency is based on SIMDA elements such as adequate internet network access, basic infrastructure and applications, all infrastructure in the form of Hardware, Software and Brainware is adequate as well as information management and processing organizations supporting organizations that are manage, provide and process information transactions and electronic documents that are sufficient so that the SIMDA Financial Application has produced financial statement information and other financial information with excellent quality relevance, excellent accuracy and very good timeliness as well.